Comparative study of the bacterial flora of the conjunctiva of newborns and cervical their mothers, and the action of silver nitrate and penicillin respectively on the conjunctival flora of newborn - Barrere G., Luciano E. (1954)
At that time, both in the ophthalmic literature and the obstetrical, there appeared a series of controversies over whether to continue using the classical method of Crede for the prevention of neo-natorum Ophthalmia with silver nitrate or replacing it with other substances, especially penicillin.